2014
DOI: 10.1016/j.imlet.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Clonal differences in IgE antibodies affect cutaneous anaphylaxis-associated thermal sensitivity in mice

Abstract: Cellular and molecular mediators of immune responses are increasingly implicated in acute and chronic pain pathophysiologies. Here we demonstrate that passive cutaneous IgE/Ag anaphylaxis provokes increased thermal sensitivity in the hind paw tissue of mice. The murine anti-DNP IgE antibodies SPE-7 and ε26 are known to induce differential cytokine production in bone marrow cultured mast cells in vitro without antigen challenge. We found a novel, antigen-dependent heterogeneity in the thermal pain responses eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The contributions of mast cells to pain pathologies have been well studied in recent years [18]. These “tunable” effectors of tissue pathology [19] are now known to contribute to protective painful responses to noxious stimuli [20,21] as well as to acute and chronic pain conditions such as migraines [22], sickle cell pain [23], irritable bowel disorders [24] and pain associated with neuropathic and neurological diseases [25,26]. Mast cell increases in vulvar biopsy samples from vulvodynia patients were first reported over a decade ago [3,27] but are not ubiquitous in all patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…The contributions of mast cells to pain pathologies have been well studied in recent years [18]. These “tunable” effectors of tissue pathology [19] are now known to contribute to protective painful responses to noxious stimuli [20,21] as well as to acute and chronic pain conditions such as migraines [22], sickle cell pain [23], irritable bowel disorders [24] and pain associated with neuropathic and neurological diseases [25,26]. Mast cell increases in vulvar biopsy samples from vulvodynia patients were first reported over a decade ago [3,27] but are not ubiquitous in all patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…The IgG receptors, FcyRs, were found to be present on human peripheral neurons as early as in foetus aged from 20 to 38 weeks , supporting a role for IgG‐FcyR in CNS development. Recent studies also reported an implication of neuronal‐Ig system in Alzheimer's disease , chronic pain , allergy and antigen‐specific autoimmune diseases . Overall, Ig sensory neuron crosstalk may serve a role in pathophysiology and, therefore, deserves closer scrutiny.…”
Section: Endogenous Triggersmentioning
confidence: 99%
“…In line with this, functionally active FcγRI and FcεRI were expressed on rodents’ superior cervical ganglion neurons and myenteric plexus neurons . Moreover, in a mouse model of cutaneous anaphylaxis; IgE‐IC drives thermal sensitivity and severe pain . IgE was also implicated in the pathogenesis of food allergy, where allergic mice showed an upregulation of FcεRI on the abdominal vagus .…”
Section: Endogenous Triggersmentioning
confidence: 99%
“…For instance, nociceptor neurons respond to inflammatory cytokines such as IL-4 as well as antibodies (58,59). Specifically, TRPV1 1 sensory neurons express the high-affinity IgE receptor FceR1 and respond to IgE-allergen immune complexes by releasing the neuropeptide SP (Substance P), which, in turn, amplifies Th2 cell production of IL-5 and IL-13 (58,(60)(61)(62). Albeit at lower surface amounts than in Th2 cells, B cell subtypes also express SP receptors.…”
Section: Toward An Integrated Model Of Airway and Lung Immune Sensingmentioning
confidence: 99%